Roles of heat shock factors in gametogenesis and development - Ryma Abane; Valérie Mezger (Wiley, 2010)
Heat shock factors form a family of transcription factors (four in mammals), which were named according to the first discovery of their activation by heat shock. As a result of the universality and robustness of their response to heat shock, the stress‐dependent activation of heat shock factor became a ‘paradigm’: by binding to conserved DNA sequences (heat shock elements), heat shock factors trigger the expression of genes encoding heat shock proteins that function as molecular chaperones, contributing to establish a cytoprotective state to various proteotoxic stress and in several pathological conditions. Besides their roles in the stress response, heat shock factors perform crucial roles during gametogenesis and development in physiological conditions. First, during these process, in stress conditions, they are either proactive for survival or, conversely, for apoptotic process, allowing elimination or, inversely, protection of certain cell populations in a way that prevents the formation of damaged gametes and secure future reproductive success. Second, heat shock factors display subtle interplay in a tissue‐ and stage‐specific manner, in regulating very specific sets of heat shock genes, but also many other genes encoding growth factors or involved in cytoskeletal dynamics. Third, they act not only by their classical transcription factor activities, but are necessary for the establishment of chromatin structure and, likely, genome stability. Finally, in contrast to the heat shock gene paradigm, heat shock elements bound by heat shock factors in developmental process turn out to be extremely dispersed in the genome, which is susceptible to lead to the future definition of ‘developmental heat shock element’.
Keywords: HSPA12A; Heat shock protein; Heat shock factor; Cell biology; Biology; Heat shock; Shock (circulatory); Transcription factor; Chromatin; Gametogenesis; Genetics; Hsp70; Gene; Embryogenesis; Medicine; Internal medicine; type of access: open access